Impact of vegetation on the methane budget of a temperate forest. Issue 3 (29th September 2018) - Plain, Caroline; Ndiaye, Fatou‐Kiné; Bonnaud, Pascal; Ranger, Jacques; Epron, Daniel
Summary: Upland forest soils are known to be the main biological sink for methane, but studies have shown that net methane uptake of a forest ecosystem can be reduced when methane emissions by vegetation are considered. We estimated the methane budget of a young oak plantation by considering tree stems but also the understorey vegetation. Automated chambers connected to a laser‐based gas analyser, on tree stems, bare soil and soil covered with understorey vegetation, recorded CH4 fluxes for 7 months at 3 h intervals. Tree stem emissions were low and equated to only 0.1% of the soil sink. Conversely, the presence of understorey vegetation increased soil methane uptake. This plant‐driven enhancement of CH4 uptake occurred when the soil was consuming methane. At the stand level, the methane budget shifted from −1.4 ± 0.4 kg C ha −1 when we upscaled data obtained only on bare soil, to −2.9 ± 0.6 kg C ha −1 when we considered soil area that was covered with understorey vegetation. These results indicate that aerenchymatous plant species, which are known to reduce the methane sink in wetlands, actually increase soil methane uptake two‐fold in an upland forest by enhancing methane and oxygen transport and/or by promoting growth of methanotrophic populations.